(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The new benzenesulfonamide type ligands: HL1 = N-[bis(diethylamino)phosphoryl]benzenesulfonamide and HL2 = N-(dimorpholin-4-ylphosphoryl)benzenesulfonamide and their sodium (NaL) and silver (AgL) salts have been synthesized. All compounds were investigated by means IR-, NMR (1H, 31P) - spectroscopy.